2018
DOI: 10.1111/tri.13127
|View full text |Cite
|
Sign up to set email alerts
|

History of psychosis and mania, and outcomes after kidney transplantation - a retrospective study

Abstract: History of psychosis or mania, if uncontrolled, both represent relative contraindications for kidney transplantation. We examined 3680 US veterans who underwent kidney transplantation. The diagnosis of history of psychosis/mania was based on a validated algorithm. Measured confounders were used to create a propensity score-matched cohort (n = 442). Associations between pretransplantation psychosis/mania and death with functioning graft, all-cause death, graft loss, and rejection were examined in survival model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 29 publications
2
25
0
2
Order By: Relevance
“…Recently, two multicenter retrospective studies from France (n = 8750) 3 and the United States using USRDS (n = 3680) 4 examined the effects of a pretransplant history of psychosis (schizophrenia or bipolar disorder) on the outcome of renal transplantation. Both studies found no evidence of increased risk of medication nonadherence, rejection, or death in these patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two multicenter retrospective studies from France (n = 8750) 3 and the United States using USRDS (n = 3680) 4 examined the effects of a pretransplant history of psychosis (schizophrenia or bipolar disorder) on the outcome of renal transplantation. Both studies found no evidence of increased risk of medication nonadherence, rejection, or death in these patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent studies on kidney transplantation have suggested that patients with a history of psychotic disorders can do well after transplantation. [2][3][4] In contrast, information regarding new-onset psychotic disorders after organ transplantation is quite limited. Some cases have been reported mainly in the context of secondary causes, such as immunosuppressant-induced adverse effects, 5 which usually manifest postoperatively, or steroid psychosis, 6 which often occurs after steroid pulse therapy administered during episodes of rejection.…”
Section: Introductionmentioning
confidence: 99%
“…7,27,[33][34][35] Figures S1-S2 shows the graphical description of the calculations for different adherence methods. Proportion of days covered (PDC) and medication persistence were calculated.…”
Section: Assessment Of Medication Adherence and Persistencementioning
confidence: 99%
“…[5][6][7] Multiple guidelines list active psychiatric illness as an absolute contraindication without a very clear definition of what constitutes an active psychiatric illness. [5][6][7] Multiple guidelines list active psychiatric illness as an absolute contraindication without a very clear definition of what constitutes an active psychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation